Synthesis, Biological Evaluation, WAC and NMR Studies of S‐Galactosides and Non‐Carbohydrate Ligands of Cholera Toxin Based on Polyhydroxyalkylfuroate Moieties. Issue 52 (21st November 2013) - Ramos‐Soriano, Javier; Niss, Ulf; Angulo, Jesús; Angulo, Manuel; Moreno‐Vargas, Antonio J.; Carmona, Ana T.; Ohlson, Sten; Robina, Inmaculada
Abstract The synthesis of several non‐carbohydrate ligands of cholera toxin based on polyhydroxyalkylfuroate moieties is reported. Some of them have been linked to D‐galactose through a stable and well‐tolerated S‐glycosidic bond. They represent a novel type of non‐hydrolyzable bidentate ligand featuring galactose and polyhydroxyalkylfuroic esters as pharmacophoric residues, thus mimicking the GM1 ganglioside. The affinity of the new compounds towards cholera toxin was measured by weak affinity chromatography (WAC). The interaction of the best candidates with this toxin was also studied by saturation transfer difference NMR experiments, which allowed identification of the binding epitopes of the ligands interacting with the protein. Interestingly, the highest affinity was shown by non‐carbohydrate mimics based on a polyhydroxyalkylfuroic ester structure.